Influences of groundwater, rainfall, and tides on beach profiles changes at Desaru beach - Abdullah, Farizul Nizam (2015)
Relationships of hydrological parameters which are groundwater level, rainfall, and tides to the beach profile changes are examined in order to advance understanding on swash zone morphology. Heavy rainfall and drought affect the groundwater level in Malaysia during these two seasons. First, heavy rainfall and storms contribute to higher groundwater level in the wet season; thereby enhance erosion. Second, lesser rainfall or no rain in the dry season will drop the groundwater level and enhances accretion. According to this phenomenon, seasonal variation factor has significant impact to the sediment transport due to groundwater level fluctuations. A field investigation is conducted at Desaru beach by doing beach profile survey, tides, and groundwater monitoring. Based on the analysis, it is found that the highest rainfall for period of November 2013 to November 2014 was occurred on December 2013, while the driest month is on February 2014 with only one day of rainfall. Observations from both monitoring wells show that the groundwater surface is generally fluctuate during Northeast monsoon, and then started to flat with time from the first inter-monsoon to second inter-monsoon. The beach groundwater levels in the two monitoring wells were affected by rainfall but groundwater level in the well that located near to the shore is highly affected by tidal fluctuation. Finally, it is found that beach with high groundwater level and high precipitation tends to erode the beach